Bioremediation of Chromium by Microorganisms and Its Mechanisms Related to Functional Groups - Abate Ayele; Yakob Godebo Godeto (Journal of Chemistry)
Heavy metals generated mainly through many anthropogenic processes, and some natural processes have been a great environmental challenge and continued to be the concern of many researchers and environmental scientists. This is mainly due to their highest toxicity even at a minimum concentration as they are nonbiodegradable and can persist in the aquatic and terrestrial environments for long periods. Chromium ions, especially hexavalent ions (Cr(VI)) generated through the different industrial process such as tanneries, metallurgical, petroleum, refractory, oil well drilling, electroplating, mining, textile, pulp and paper industries, are among toxic heavy metal ions, which pose toxic effects to human, plants, microorganisms, and aquatic lives. This review work is aimed at biosorption of hexavalent chromium (Cr(VI)) through microbial biomass, mainly bacteria, fungi, and microalgae, factors influencing the biosorption of chromium by microorganisms and the mechanism involved in the remediation process and the functional groups participated in the uptake of toxic Cr(VI) from contaminated environments by biosorbents. The biosorption process is relatively more advantageous over conventional remediation technique as it is rapid, economical, requires minimal preparatory steps, efficient, needs no toxic chemicals, and allows regeneration of biosorbent at the end of the process. Also, the presence of multiple functional groups in microbial cell surfaces and more active binding sites allow easy uptake and binding of a greater number of toxic heavy metal ions from polluted samples. This could be useful in creating new insights into the development and advancement of future technologies for future research on the bioremediation of toxic heavy metals at the industrial scale.